Unveiling the Healing Rituals of Spirit Media (Pari Khan) in Chitral: A Dramaturgical Analysis - Ahmad, Zafar; Nawab, Habib Ullah; Ali, Sajid (Annals of Human and Social Sciences, 2023)
This study explores the healing rituals of Spirit Media (Pari Khan) in Chitral, Pakistan, using Goffman's Dramaturgical Analysis and Lew's Sex War theories. The research encompasses comprehensive data obtained from extensive interviews conducted with spirit mediums, their assistants, clients, shamans, therapists, and those impacted by spirit possession. Additionally, participant observations of therapeutic rituals in their authentic settings supplement this data. The research analyses the performative nature of spirit media, portraying them as the conduits via which spirits communicate information. Throughout these therapeutic rituals, spirit media establish a profound spiritual bond by skillfully manipulating images, controlling information, and creating an aura of mystery during their performances. By strategically positioning religious objects and assuming specific roles, they provide impactful revelations that captivate the clients seeking spiritual restoration. These women assume the positions of healers, allowing them exemptions from their regular household chores and elevating their status to that of matriarchs in their households. Within the traditionally male-dominated society of Chitral, this advancement often results in monetary advantages, signifying a significant change in socioeconomic dynamics. Through the use of Goffman's Dramaturgical Analysis, we observed the interplay of "backstage" and "frontstage" dynamics in these ceremonies. A profound sense of spiritual interconnectedness arises from the meticulous coordination of one's environment, appearance, and behaviour. Clients are driven to seek a range of services, including healing and settling domestic difficulties, due to their belief in spirits and the fascinating performances of spirit media. The study's recommendations emphasize the significance of cultural comprehension, ethical principles, integration of traditional healing into modern healthcare systems, addressing gender dynamics, enhancing community awareness, and promoting further collaborative research that connects cultural practices with contemporary knowledge.